Relaxable Damage in Hot-Carrier Stressing of n-MOS Transistors - M. Rahmoun; E. Bendada; A. El Hassani; K. Raïs (Active and Passive Electronic Components)
A method for device characterization is experimented to qualify the relaxable damage in hot-carrier stressing of n-MOS transistors. The degradation of physical parameters of the body-drain junction of power HEXFETs is presented for applied stress condition Vg= Vd/2. Large decrease of the resistance series, of the ideality factor, and of the reverse recombination current are shown to be related to relaxation time, and are significant at Vg=–Vd. These effects are discussed and explained by the evolution of the interface states.